Unpacking the anti-fibrotic arsenal: molecular mechanisms and therapeutic translation of MSC-derived exosomes in pulmonary fibrosis - Xiao, Yijia; Hoorain, Iqra; Zhang, Lin; Bellusci, Saverio; Jin, Xuru; Yang, Hongzhong; Zhang, Jin-San (Frontiers in Immunology, 2025)
Pulmonary fibrosis (PF) is a progressive, fatal interstitial lung disease with a dire prognosis and limited therapeutic options. Current standard-of-care anti-fibrotic agents (e.g., nintedanib and pirfenidone) offer only modest efficacy in slowing disease progression. Mesenchymal stem cell-derived exosomes (MSC-Exos) have recently emerged as a promising cell-free therapeutic strategy, boasting superior biocompatibility, low immunogenicity, enhanced biodistribution, and an innate tropism for injured tissues. Their potent anti-fibrotic effects are mediated through multiple mechanisms: targeted homing to fibrotic niches; reprogramming of dysregulated immune responses, notably by shifting macrophage polarization from a pro-inflammatory (M1) to an anti-inflammatory/reparative (M2) phenotype; suppression of pathological extracellular matrix deposition via inhibition of core fibrogenic pathways; and alleviation of endoplasmic reticulum stress in alveolar epithelial cells. This review systematically delineates the biological functions and molecular mechanisms underpinning the therapeutic actions of MSC-Exos in PF. We further evaluate completed and ongoing clinical trials (2014–2024), appraise the current translational landscape, and identify persistent challenges in drug development. Ultimately, this integrative analysis aims to define the mechanistic basis of MSC-Exos' efficacy, evaluate their clinical trajectory, and provide a strategic roadmap for their development into precision nanotherapeutics for PF.